Impella RP versus pharmacologic vasoactive treatment in profound cardiogenic shock due to right ventricular failure: Unloading and end-organ perfusion in a large animal model. (26th April 2021) - Josiassen, J; Helgestad, OKL; Udesen, NLJ; Banke, A; Frederiksen, PH; Schmidt, H; Jensen, LO; Hassager, C; Moeller, JE; Ravn, HB
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation Unrestricted research grant from Abiomed Background: No strong evidence exists regarding the treatment of cardiogenic shock (CS) caused by acute right ventricular (RV) failure which has mainly consisted of vasoactive drugs. There is expert agreement that treatment with the recently developed Impella RP is feasible, but no previous studies have compared vasoactive treatment strategies with the Impella RP in terms of cardiac unloading and end-organ perfusion. Hypothesis Treatment with the Impella RP device will be associated with lower RV myocardial workload (pressure-volume area) compared to vasoactive treatment strategies and can furthermore be achieved without compromising organ perfusion. Methods: CS was induced by a stepwise injection of polyvinyl alcohol microspheres into the right coronary artery in twenty adult female Danish landrace pigs weighing 75-80 kg. After induction of CS, the pigs were allocated to one of the two interventions for 180 minutes: 1) vasoactive therapy comprised a continuous infusion of norepinephrine (0.1 µg/kg/min) for the first 30 minutes, supplemented by an infusion of milrinone (0.4 µg/kg/min) for the remaining 150 minutes or 2) immediate insertion of and treatment with the Impella RP. The results are presented as median [Q1;Q3]. Results: Treatment with the Impella RP was associated with a lower RV workload compared to the vasoactive group, while no difference was observed with regards to left ventricular workload among intervention groups, Figure 1. Renal venous oxygen saturation increased to a similar degree following both interventions compared to the state of CS. A trend towards a higher cerebral venous oxygen saturation was observed with norepinephrine compared to Impella RP (Impella RP 51 [47;61] % vs Norepinephrine 62 [57;71] % ; p = 0.07), which became significantly higher with the addition of milrinone (Impella RP 45 [32;63] % vs Norepinephrine +Milrinone 73 [66;81] %; p = 0.002). Conclusion: In this large animal model of profound CS caused by predominantly RV failure the Impella RP unloaded the failing RV. The vasoactive treatment, however, caused a higher cerebral venous oxygen saturation, while both interventions increased renal venous oxygen saturation to a similar degree.